2014
DOI: 10.1021/ac500340t
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Structural Characterization of N-Linked Glycopeptides Using Complete Derivatization for Carboxyl Groups Followed by Positive- and Negative-Ion Tandem Mass Spectrometry

Abstract: Tandem mass spectrometry (MS/MS or MS(n)) is a powerful tool for characterizing N-linked glycopeptide structures. However, it is still difficult to obtain detailed structural information on the glycan moiety directly from glycopeptide ions. Here, we propose a new method for in-depth analysis of the glycopeptide structure using MS/MS. This method involves complete derivatization of carboxyl groups in glycopeptides. Methylamidation using PyAOP as a condensing reagent has been optimized for derivatizing all carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 47 publications
1
50
0
Order By: Relevance
“…[20][21][22] While these approaches have indeed shown improved sialylation analysis by MS, and can achieve recognition of sialic acid linkage upon fragmentation, no report has been made of a glycopeptide derivatization that reacts in a selective way to differently linked sialic acids.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] While these approaches have indeed shown improved sialylation analysis by MS, and can achieve recognition of sialic acid linkage upon fragmentation, no report has been made of a glycopeptide derivatization that reacts in a selective way to differently linked sialic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Derivatization of carboxyl groups by methylamine using the condensing reagent (7-azabenzotriazol-1-yloxy)-tripyrrolidinophosphonium hexa uoro-phosphate (PyAOP) was applied by Nishikaze et al to conduct glycopro ling. 154) ey found that positive-ion CID of derivatized glycopeptides mainly provided information on peptide sequence and glycan composition, whereas negative-ion CID provided in-depth structural information on glycan moieties. PSD and CID were combined by Lattova et al to pro le derivatized N-linked glycans from ovalbumin.…”
Section: Fragmentation Methods For the Structural Analysis Of Carbohymentioning
confidence: 99%
“…For example, ion mobility MS was used to separate and analyze intact ovomucoid glycopeptides (40) and urine glycopeptides from a patient diagnosed with Schindler disease (129). Furthermore, recent studies have explored the feasibility of measuring deprotonated glycopeptides in negative ion mode with (130) and without (131) derivatization. Innovative strategies for the derivatization of sialic acid residues have also been designed to achieve linkage-specific (␣2,3 versus ␣2,6-sialyl) information at the glycopeptide level (132) and to obtain more equal ionization response from neutral and sialylated glycopeptides (133).…”
Section: Ms Acquisition Strategies In Glycoproteomics-lc-ms/mentioning
confidence: 99%